A construção e a percepção do tempo nas obras 1919 e O bandido da luz vermelha - Cristiano Elias de Paulo (2017)
The present work intends to analyze two works, one cinematographic, the other literary with the intention of shed some light on issues related to studies about time, literature and cinema. However we will take as a starting point a less intense analysis about philosophy, so it will not be the intention of this dissertation a broader approach with regard to the studies on the time in philosophy, this will explain, therefore the absence of some authors like Bergson, Heidegger and the approach less time consuming work of others like Deleuze. The general objective of this dissertation was to explain the relationship of time in film and literature using, for others, John dos Passoss novel, 1919, and Rogério Sganzerla' s film, O Bandido da Luz Vermelha.